Profile of Patients Visiting a Surgical Eye Camp in Pokhara, Nepal - A Descriptive Cross Sectional Study - Shrestha, Ram; Chhetri, Suchit Thapa; Rajkarnikar, Sagar; Rajbhandari, Ajay; Shrestha, Oshan; Khadka, Sitaram (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: Nepal is a lower-middle-income country with low health literacy and challenging healthcare access. Various health camps are conducted throughout the country to address these needs. This study was conducted to understand the demographic and clinical profile of patients visiting a surgical eye camp in Pokhara, Nepal. Methods: A cross-sectional study was conducted among 945 patients visiting the eye camp at Military Hospital, Pokhara, Nepal. Descriptive statistics were used to present the demographic details and clinical profile of the patients. Results: The demographic profile of the participants showcased a diverse sample regarding age group, gender, and ethnic group. Among the total 945 patients, 306 (32.38%) had prior ophthalmological conditions, with presbyopia (25.49%) and refractive errors (15.03%) being the most common. During the camp, prevalent diagnoses included presbyopia (27.39%), refractive errors (22.23%), and cataract (16.10%). Only 45.75% of previously diagnosed patients were on regular follow-ups. Conclusion: Different types of eye disorders are prevalent among general population. Presbyopia and refractive errors are the commonest eye disorders in the study population.